Development of responsibility attitude competency assessment instruments for vocational high school students - Mujiyono Mujiyono; Ari Setiawan; Makmur Haji Harun (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to obtain a standardised responsibility attitude competency assessment instrument to measure the value of responsibility attitude competencies of students of SMK Negeri 8 Purworejo and to determine the results of the implementation of responsibility attitude competencies in students of SMK Negeri 8 Purworejo Central Java as measured by the assessment instrument developed so that the level of responsibility attitude value of SMK Negeri 8 Purworejo students can be known. This research is development research. The development stages were carried out with expert judgment validation, first revision, readability test, second revision, content validity test, construct validity test, third revision, final assessment instrument, and implementation of the final assessment instrument. The content validity test used the Aiken index. Reliability was tested with Cronbach Alpha formulation. Construct validity test used factor analysis. After preparing the assessment model and the pilot test, it was concluded that an assessment instrument was obtained to measure the attitude of responsibility as many as 50 items, consisting of 25 valence (attitude) items and 25 factual (behaviour) items. Second, the indicators of the attitude of responsibility assessment instrument are (a) Carrying out individuals well, (b) Accepting the risks of actions taken, (c) Doing tasks according to procedures, (d) Returning borrowed items, and (e) Doing group works together. Third, it measured the attitude of responsibility of 72 students of SMK Negeri 8 Purworejo with the measurement results in the Very High category.